Prospective Cohort Validation Study of a Novel Foot Offloading Device - Ryan Lubarsky, BA (Wolters Kluwer, 2021)
Summary:. Pressure offloading is often considered a crucial factor affecting healing after a foot injury. We have devised a novel foot offloading device (PopSole) which allows for immediate customization of the area where there is foot pain and allows for adjustable arch support and metatarsal pad height while maintaining patient stability. We hypothesize that pain and function outcomes will improve significantly after use of the device over a 1-month period. Ten participants with foot pain for longer than 6 months completed five validated outcome questionnaires during three visits (initial screening, at 2 weeks, and at 4 weeks). Devices were deflated in areas of pain specific for each patient. Validated patient reported outcomes measures showed significant improvement in pain and function from baseline to week two (r = 0.644, P < 0.05), (r = 0.43, P < 0.05), and (r = 0.552, P < 0.05), respectively, and the Foot & Ankle Ability Measure (FAAM) showed improved ability in activities of daily living (r = 0.58, P < 0.05) and sports (r = 0.69, P < 0.05). All 10 patients reported pain relief during at least one visit and/or an ability to return to standing-based activities that they previously were unable to do. PopSole rapidly improved pain and function, with sustained relief through 4 weeks. Current studies are in progress to assess long-term durability of the device and potential modifications to be made before future randomized studies to assess pressure and gait assessment, shear forces, and diabetic foot ulcer mitigation.